PERAN PETANI DALAM PENERAPAN PEMUPUKAN BERIMBANG PADA TANAMAN JAGUNG HIBRIDA (Zea Mays L.) DI MOJOSONGO, BOYOLALI - Sujono, Sujono (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2018)
The research was conducted in Manggis, Mojosongo, Boyolali with the purpose of identifying farmers role on balanced fertilization implementation for Hybrid Corn (Zea mays L.) cultivation. Descriptive analysis was used in the research, corn farmers residing in Manggis as its population. Probability sampling was the chosen technique, and farmer groups were determined purposively. Four farmers groups out of six were chosen, further samples were drawn by simple random sampling resulting in 30 respondents. The research results showed high farmer, stakeholder and production supplier roles on balanced fertilization implementation for Hybrid Corn, however Farmers role on providing capital was low. With this research, balanced fertilization technology for Hybrid Corn is expected to be constantly improved. As for farmers as capital providers, they are expected to decrease their dependence on other parties.